Rijeka and its surroundings in 1918-1919 : the public impact and the image of the epidemic - Doričić, Robert (Array, 2019)
The Spanish flu, one of the worst epidemics in history, appeared in 1918, on the eve of the end of the World War I. The characteristic of the epidemic on the territory of the city of Rijeka has been poorly studied. Certainly, the lack of primary sources, such as hospital registries, have made the understanding of the incidence and the course of the epidemic in the city more difficult. Therefore, the death certificates have emerged as the main primary source. The purpose of this paper is to explore and describe mortality caused by the (Spanish) flu during 1918 and at the beginning of 1919, using the death registers of those who lived in the area of the city center and the surrounding parishes. The results of the Spanish flu mortality research in the area of Rijeka are compared to the Spanish flu specific mortality on the territory of the three parishes situated in the wider area of Rijeka – Brseč, Mošćenice and Lovran. The elucidation of the characteristics of the Spanish flu epidemic and its impact on the quotidian life in the city of Rijeka is possible through the analysis of daily newspapers as well. In this paper, we have explored such articles in the La Bilancia, Rijeka’s newspaper published in Italian.